THE TEACHERS' CLINIC. - Garner, S. Paul (The Accounting Review, 1948)
As a result of a recent discussion between members of the Executive Committee of the American Accounting Association and the Chairman of the Education Committee of the Institute of Internal Auditors in the United States, the editor to this department was asked to conduct a limited survey in order to determine the present status of the course in internal auditing. The Institute of Internal Auditors has been active in the field of education for several years, and its several committees wish to cooperate in every way possible to further tile adequate preparation of students for careers in internal auditing. Some case and text materials have already been prepared, these teaching aids are rapidly being augmented as more universities become interested in the subject matter. In carrying out the survey 36 questionnaires were sent to specific persons in the same number of selected institutions. Most of the prominent schools of commerce and business administration were included in the group and thirty replies were received.